Kinetic study of the nopol synthesis by the Prins reaction over tin impregnated MCM-41 catalyst with ethyl acetate as solvent (2015)
ABSTRACT: The kinetics of the catalytic synthesis of nopol from b-pinene and paraformaldehyde over Sn-MCM-41 catalyst and using ethyl acetate as solvent is presented and compared with previous studies in toluene. Reaction rate data were fitted to a kinetic expression based on the Langmuir–Hinshelwood formalism, using the initial rates method. Reaction rate constant and adsorption constants were determined by regression of experimental data. The highest adsorption constant for nopol respect to reactants (KC = 14.948 M-1) allows to explain the strong inhibition effect of this compound that is experimentally observed. Solvent effects were discussed in terms of formaldehyde solubility, solvation of activated complex and reactants, and competitive adsorption on active sites. Higher solubility of formaldehyde in ethyl acetate respect to toluene, determined with Henry’s law, along with the competitive adsorption of solvent and a more probable solvation of b-pinene and nopol may explain the better selectivity in ethyl acetate. Dependency of reaction constant on temperature was evaluated between 75 °C and 90 °C, resulting in an apparent activation energy of 98 kJ mol-1, which is higher than in toluene, suggesting stabilization of carbocation intermediates by solvation in the polar ethyl acetate solvent.